The Last Nizam - The Rise and fall of India's Greatest Princely - John Zubrzycki (London PICADOR, 2012)
This is a lucid and compelling history of one of India's most wealthy dynasties and one of its most controversial royals. "The Last Nizam" is the story of an extraordinary dynasty, the Nizams of Hyderabad, and how the heir to India's richest princely state gave up a kingdom and retired to the dusty paddocks of outback Australia. With vivid detail and anecdote John Zubrzycki charts the rise of the Nizams to fabulous wealth and prominence under the Mughal emperors of India, giving a rich and vibrant portrait of a realm soaked in blood and intrigue. Above all he describes the strange - sometimes comic, sometimes tragic - life of Mukarram Jah, His Exalted Highness, the Rustam of the Age, the Aristotle of the Times, Wal Mamaluk, Asaf Jah VIII, the Conqueror of Dominions, the Regulator of the Realm, Nawab Mir Barakat Ali Khan Bahadur, The Victor in Battles, the Leader of Armies, the last Nizam, the man who left behind the diamonds of Golconda and the palaces of Hyderabad to drive bulldozers in the Australian bush. A delicate and detailed work, "The Last Nizam" adds a crucial chapter to the history of India, capturing the very scent of wine, women and wealth whose appetites kept the Nizams in news and scandal while simultaneously deepening their legend.
Keywords: Biography -- Biography; Indian History -- Indian History